Respuesta :
This can be rewritten as
(x -6)² = 90 . . . . . the left side is already a perfect square
x -6 = ±√90 . . . . . take the square root
x = 6 ±3√10 . . . . add 6
(x -6)² = 90 . . . . . the left side is already a perfect square
x -6 = ±√90 . . . . . take the square root
x = 6 ±3√10 . . . . add 6
Answer:
Using the identity rule:
[tex](a-b)^2 = a^2-2ab+b^2[/tex]
Given the equation:
[tex]x^2-12x+36 = 90[/tex]
Rewrite the above equation as:
[tex]x^2-2 \cdot x \cdot 6+6^2 = 90[/tex]
Apply the identity rule:
[tex](x-6)^2 = 90[/tex]
Take square root to both sides we have;
[tex]x-6 = \pm \sqrt{90}[/tex]
Add 6 to both sides we have;
[tex]x = 6\pm \sqrt{90}[/tex]
or
[tex]x = 6 \pm 3\sqrt{10}[/tex]
Therefore, the value of x are:
[tex]6+3\sqrt{10}[/tex] and [tex]6-3\sqrt{10}[/tex]